Democracy and the new religious pluralism/ edited by Thomas Banchoff - "Banchoff, Thomas (ed.)" (Oxford, 2007)
In this book, a group of leading scholars - including Peter Berger, John Esposito, Robert Wuthnow, Martha Nussbaum, Diana Eck, Stanley Hauerwas, and Miroslav Volf - examines the new religious pluralism and the challenges it poses for democratic societies on both sides of the Atlantic.
Keywords: Democracy-religious aspects